Faktor yang Mempengaruhi Keberhasilan Penerapan Teknologi Bidang Jalan dengan Kontrak Rancang Bangun - Hendrawan, Hendra (MEDIA KOMUNIKASI TEKNIK SIPIL, 2018)
Research and development in the roads sector is one of the coaching tasks of roads authority. To disseminate the results of research or technology that has been developed required the transfer of technology which one of them through technology implementation project. In the Year 2015-2017 Institute of Road Engineering has carried out the technology transfer process through limited project of implementation technology  by using Design and Build contract. In the implementation project there are some constraints or factors that affect the implementation performance so that the resulting output is not optimal. The purpose of the study is to identify the critical determinants of project success of technology implementation with Design and Build contract and to give weighting. The method used in the study is descriptive qualitative analysis using data collection tools in the form of interviews and questionnaires to further analyzed by Analytical Hierarchy Process method. The results of the study showed that the factors that affect the successful of implementation technology projects is qualification of providers. The sub aspect that is considered has big influence is the financial ability for the qualification aspect, and the basic knowledge to the technology developed for technical aspect.